Anger Managed : Using Music Therapy Techniques at the County Jail - Benz, Rachel; Weiss, Kim (My University, 2011)
The goal of this presentation was to inform fellow student music therapists who have not had music therapy experience in a forensic setting about providing music therapy services in a jail setting with many safety rules limiting types of activities and materials which are allowed.
Color poster with text and image.
Keywords: Music therapy--Instruction and study; Music therapy--Research--Methodology; Prisoners--Mental health services--United States; Posters